A proactive energy awareness traffic routing for wireless sensor networks against energy sink-holes - Mustafa, Mayada Salih Abdalla (2019)
Tree topology-based traffic routing in WSNs imposes a heavy burden on its root nodes which quickly results in energy hole formation and eventually sink isolation and network partitioning, which are undesirable. In the literature, proactive approaches that avoid such a formation, particularly with random node distribution, has not been extensively explored. In this thesis, cooperative communication based on tree topology construction is proposed to address energy and routing decision challenges in WSNs with single and multiple sinks. This is adopted in the proposed balanced energy-hole prevention method in tree topology (EBEHA-T) with a single sink. Next, the problem of large variations in energy consumptions with multiple sinks in merging tree-based multiple energy hole alleviation algorithm (MEHA-MT) is addressed. This is a topology construction-based cooperative routing in which alternate routes are found that avoid data delivery to heavily loaded sinks which subsequently precludes sink isolation and network partitioning. Finally, this thesis proposes a collaborative approach among multiple static sinks to achieve balanced energy among the nodes in the network resulting in improved reliability. Here, a centralized controlled multiple sink-rooted tree coordinates traffic delivery to the sink with respect to a reference energy balance pattern; this is referred to as COMEHA for centralised control-based multiple-energy hole alleviation. OMNeT++ simulator has been used to conduct performance evaluations of the above algorithms. Results show an increase in network energy balance and reduction in average energy consumption for EBEHA-T, in the range of 78% and 51%, respectively, against reactive approaches. For MEHA-MT, energy balance achieved were 46% and 60% of two sinks, compared against multiple topology-based traffic routing cooperation. Finally, COMEHA enhances work efficiency to 0.54 and increases energy balance to 21% compared with conventional schemes. Overall results show immunization against energy hole formation during transmission, which results in extended lifetime in WSN.